Science and technology consortia in U.S. biomedical research: A paradigm shift in response to unsustainable academic growth. (12th November 2014) - Balch, Curt; Arias‐Pulido, Hugo; Banerjee, Soumya; Lancaster, Alex K.; Clark, Kevin B.; Perilstein, Michael; Hawkins, Brian; Rhodes, John; Sliz, Piotr; Wilkins, Jon; Chittenden, Thomas W.
<x xml:space="preserve">Abstract</x> Science and technology consortia provide a viable solution for the recent unsustainable academic growth in biomedical research. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>